Efficacy of Brief Intervention for Alcohol Consumption during Pregnancy in Argentinean Women: A Randomized Controlled Trial - Gimenez, Paula Victoria (2022)
Introduction: Although Brief Intervention (BI) has proven to reduce alcohol consumption during pregnancy in high income countries, there is no evidence from the Southern Cone of America. Thus, we conducted a study to assess BI efficacy among Argentinean pregnant women. Method and Materials: We collected data on pregnant women receiving prenatal care at the public health system in Mar del Plata, Argentina. Women with less than 26 weeks of gestation (n = 486) were randomized to brief advice (BA) or BI. Three months later they were re-assessed; women with more than 26 weeks of gestation constituted a screening only control group (SC) (n = 154). Self-reported quantity and frequency of alcohol consumption, frequency of binge drinking, and related problems after three months were used as outcomes. We performed generalized estimating equations and clinical significance analyses. Also, we obtained newborn health indicators from the city’s health system database to use as objective outcomes. Women who did not participate in any of the three former conditions were randomly selected to constitute a non-screening control group (NSC) (n = 150). We compared objective outcomes among BI, BA, and NSC groups using the Wilcoxon rank test. Results: In comparison with SC, BI and BA reduced alcohol consumption, without differences between the latter two. Newborns of women who received BI and BA had better health indicators compared with the NSC group. Conclusions: performing either a BI or BA reduces alcohol consumption among Argentinean pregnant women and might lead to healthier newborns.